Peran Mahasiswa Dalam Memberikan Bimbingan Perbaikan Bacaan Al Quran (Studi Kasus Di Desa Sidodadi Kec. Kejuruan Muda Kab. Aceh Tamiang) - Pujiono, Tri; Fahriansyah, Fahriansyah; Irfan, Muhammad; Zacky, Adelfi (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
Difficulties in reading the Koran experienced by children with special needs have not received attention from teachers and parents. This is a condition of concern and is a concern for researchers to take actions that can change conditions. The parents of the children from the sidodadi village go to work every day in the morning and return home in the afternoon, their days are spent more in the fields than at home so time is rarely given to children to guide reading the Qur'an. Considering that the majority of residents of the sidodadi village only graduated from junior high and high school so there are still very few teachers or teaching staff there and the lack of teaching methods or strategies used to guide children to read the Qur'an so that children easily feel bored. Therefore, there are students who serve there to help and guide children in reading the Qur'an and to motivate children to have a high spirit in learning let alone learn to read the Qur'an under any conditions. The role of students who serve in the village of Sidodadi Village is to guide children in reading the Qur'an. Teaches how to pronounce the correct letter makhorijul and the science of recitation and the short length of reading the Qur'an. With the guidance of a teacher, children will become more focused in reading the Qur'an in accordance with the science of recitation. The importance of guiding children in reading the Qur'an at an early age because it can give attention to children's ability to read the Qur'an properly and correctly.